RANCANG BANGUN SISTEM ADMINISTRASI KERJA PRAKTEK DAN TUGAS AKHIR BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Subari, Arkhan; Tadeus, Dista Yoel; Winarno, Heru; Yuwono, Teguh (Vocational School Diponegoro University, 2018)
Information system is a set of components that interconnect, collect, process, store, and distribute information to support decision making and supervision within an organization. Today the information system can not be separated with computer technology that feels growing rapidly along with our increasingly complex needs. These developments can be seen from the many organizations or institutions in various fields that use computerized systems to perform various jobs quickly and with great accuracy. The use of computerized systems is expected to minimize errors made by humans thereby reducing large losses. And can mengefisienkan time in completing the work quickly and accurately. One concept of building a computerized information system is dengfan MVC model. Model-View-Controller (MVC) is a concept introduced by the inventor of Smalltalk (Trygve Reenskaug) to encapsulate data along with processing (model), isolate from the process of manipulation (controller) and view to be represented on a user interface . The MVC architecture has the benefit of separating between model and view allowing multiple views using the same model. As a result, an application model component is easier to implement, test, and maintain, because all access to the model runs through this component. One of the frameworks that works based on the MVC concept is Codeigniter. Codeigniter is an open source web application framework that is used to build dynamic php applications. The main purpose of Codeigniter development is to help developers to work on applications faster than writing all the code from scratch. Because of the superiority of codeigniter that the system of practical work administration and the final task is built using the framework..